Style of Teaching Influence and Motor Educability Against Learning Outcomes of Serve Under Volleyball - Sirait, Zuhri Himawan (LPPM Universitas Primagraha, 2020)
The purpose of this research is to know the influence of a style of teaching and motorcycle educability learning of the results of serve under volleyball on the kids class VII public junior high schools aek ledong 1. The study is done at aek ledong smpn 1. This research uses experimental methods with the treatment by level 2 x 2 .The sample collection using clusters of random sampling. The total sample some 40 people and is divided into four groups with each group of 10 people. Data analysis using analysis of variance ( anova ) and advanced test by test tukey. This study concluded that: (1) As a whole , there are differences between the style of teaching reciprocals with the style of teaching exercise study results to serve under volleyball, (2) There is an interaction between the teaching and learning educability motorcycle broke down on the outcome of volleyball, (3) For students who have motor educability high , the provision of the style of teaching reciprocals give more influence than with the style of teaching good exercise to serve under volleyball study results, (4) For students who have motor educability low , the provision of the style of teaching exercise influence better compared with the style of teaching and learning of the reciprocals serve under volleyball volleyball.